2019
DOI: 10.1111/aos.14315
|View full text |Cite
|
Sign up to set email alerts
|

Vascular changes after vitrectomy for rhegmatogenous retinal detachment: optical coherence tomography angiography study

Abstract: To analyse the postoperative foveal avascular zone (FAZ) area, superficial vessel density (SVD) and deep vessel density (DVD) and their correlation with functional (best-corrected visual acuity, BCVA) and anatomical outcomes (foveal macular thickness, FMT) after surgery for rhegmatogenous retinal detachment (RRD) repair. Method: Patients with RRD eyes, successfully treated with a single pars plana vitrectomy (PPV) with gas tamponade and a minimum 12 months follow-up, were re-examined. Foveal avascular zone (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 29 publications
8
89
2
Order By: Relevance
“…Our results build on the few recent reports that have investigated mac-off RRD eyes following repair using OCT-A. 28,29,31,32 We herein explore the various suggested mechanisms for the microvascular changes observed even following surgical repair of RRD including the effect of the RD itself, the effect of our surgical intervention for RD repair and the effect of macular detachment on the retinal microvasculature. A neurosensory RD is thought to lead to outer retinal ischemia, although the exact mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our results build on the few recent reports that have investigated mac-off RRD eyes following repair using OCT-A. 28,29,31,32 We herein explore the various suggested mechanisms for the microvascular changes observed even following surgical repair of RRD including the effect of the RD itself, the effect of our surgical intervention for RD repair and the effect of macular detachment on the retinal microvasculature. A neurosensory RD is thought to lead to outer retinal ischemia, although the exact mechanism is not completely understood.…”
Section: Discussionmentioning
confidence: 64%
“…It has been extensively investigated in macular degeneration, retinal vein occlusion, diabetic retinopathy, posterior uveitis and optic neuropathies. [22][23][24][25][26][27] Recently, few reports investigated OCT-A parameters after mac-on [28][29][30] or mac-off 28,29,31,32 RD repair including vascular density (VD) and FAZ area and correlated those with visual function. Building on those reports, we herein employed OCT-A to evaluate microvascular changes in the superficial (SCP) and deep capillary plexuses (DCP), choriocapillaris and the FAZ area and their correlation with final best corrected visual acuity (BCVA) in eyes after mac-off RRD repair using the fellow eyes as controls.…”
Section: Background and Objectivementioning
confidence: 99%
“…These contradicting results can be explained by differences in control groups. Identical to our study, Bonfiglio et al 19 measured the healthy fellow eye of the macula-off RRD patients as control. This method is appropriate because the FAZ has been shown to be similar in both eyes of healthy volunteers, but varies among individuals.…”
Section: Discussionmentioning
confidence: 77%
“…The current literature reports contradicting results regarding the FAZ after surgery for macula-off RRD. One study 19 reported no difference in FAZ between macula-off RRD eyes and control eyes, and two other studies 15,17 reported larger FAZ in macula-off RRD eyes compared with control eyes. These contradicting results can be explained by differences in control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation